Kant’s discovery of normativity (Diametros, 2004)
Until the eighteenth century most European normative positions in moral philosophy presupposed strong motivational internalizm. According to this assumption a belief about the good leads to action in accordance with it because the belief brings about a desire to act in this way or it is identical with this desire. Strong internalizm is exposed to fundamental difficulties. It cannot explain incontinence (the so-called weak will) and justify obligations for those who have not assented to (correct) beliefs about the good. An analysis of the Groundwork for the Metaphysics of Morals and Critique of Practical Reason shows that Kant departed from strong internalizm in favor of its weak version. Drawing a clear line between facts and desires (the sphere of the empirical) and beliefs about the good (the sphere of the rational), Kant holds that a belief about the good does not necessarily lead to an appropriate action but may require a special motive. For this reason Kant distinguishes between facticity and normativity, for which purpose he analyses the concept of duty. This concept allows him to grasp the particular phenomenon of necessitation that is associated with beliefs about the good without presupposing that these beliefs will lead to actions which accord with them. In developing his conception of acting from duty Kant explains the possibility of both acting on beliefs about the good and of diverting from them This “discovery” of normativity has important consequences for moral theory and practice. Among other things, it requires a distinction between moral and other goods by identifying moral good with unconditional good.